Research Trends of Career Construction in Vocational Education: A Bibliometric Review - Rivaldy, Deries; Komaro, Mumu (Fakultas Teknik Universitas Negeri Malang, 2022)
The rapidly changing work environment and work patterns require individuals to actively adapt to the challenges and difficulties that arise in their career development. Over the past 20 years, construction theory has become prominent in career psychology. The concept of career construction is an adaptation model that explains the process of career construction over a person's life span through adaptation. Therefore, the career adaptation model describes the interaction between stable personal characteristics, psychological capacities, career behavior, and career outcomes. Career results will be optimal if achieved with adequate career behavior and facilitated by psychology. The purpose of this research article is to provide an overview of trends in career construction in Vocational Education to understand the evolution in the field of career construction from 2005 to 2022. The research method uses the bibliometric method. The amount of data obtained is 400 articles from publications indexed in the Scopus database. The research describes citation analysis, co-authorship analysis, co-citation analysis, and keyword analysis that produces a pattern of research maps in the field of Education. up-to-date for research on future career construction